Implementing virtual private networks - Steven Brown (McGraw-Hill, 2000)
This book is written in three part. Part 1 presents the fundamentals of VPN technology. Part 2 is the next logical step in VPN technology: The basics, installing a VPN, troubleshooting VPNs, maintaining a VPN. This third part of the book discusses security with VPNs.